Centralized pain and pain catastrophizing mediate the association between lifetime abuse history and self-reported pain medication side effects. Issue 4 (26th January 2020) - Pierce, Jennifer; Hassett, Afton L; Schneiderhan, Jill R; Divers, Jude; Brummett, Chad M; Goesling, Jenna
Abstract : Background: Self-reported side effects of pain medication are important determinants of treatment course that can affect patient adherence, medication discontinuation and physician decisions. Yet, few studies have investigated patient-level predictors of self-reported pain medication side effects. The present study sought to fill this gap by exploring the impact of physical or sexual abuse history on self-reported pain medication side effects and considered a mediation model in which those effects are transmitted through a centralized pain phenotype and pain catastrophizing. Methods: We conducted a cross-sectional analysis of 3118 patients presenting to a tertiary-care, outpatient pain clinic. Results: Approximately 15% of the sample (n=479) reported a lifetime history of abuse. Patients with a lifetime history of abuse, particularly abuse that occurred in both childhood and adulthood, reported more pain medication side effects compared with patients reporting no abuse history. Furthermore, path analysis showed that a centralized pain phenotype and pain catastrophizing mediated the association between lifetime abuse history and the sum of pain medication side effects. Conclusions: This suggests that individuals who experience abuse may develop a heightened physiological sensitivity to stimuli, as well as a tendency to interpret stimuli negatively, exaggerate the impact of aversive stimuli and undermine their ability to cope with the stressor. This study highlights the need for physicians to understand patient-level predictors of medication tolerance and to consider a history of abuse and trauma in decisions regarding treatment and medication management.